Perceptions around teachers social support with student achievement motivation - Oktasari, Maria (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2017)
Several indications that indicate student in low achievement motivation, among others: (1) lack of enthusiasm to follow the lesson, (2) less attention to the teacher, (3) the students have not targeted yet, (4) students tend to ignore the task, (5) (6) students are less harmonious with teachers, (7) students are lazy to learn, and (8) some students feel scared with the teacher. Students perceptions of teachers social support are factors that allegedly influence students achievement motivation. This study aims to determine the relationship of students perceptions of the social support of teachers with achievement motivation. The method used throughout this research is quantitative with regression technique. Samples numbered to 206 students of SMA Negeri 1 V Koto Timur Padang Pariaman, and selected by proportional random sampling. The instrument used is the students perception scale of teachers social support and achievement motivation. The research findings indicate that there is a significant correlation between around teachers social support with student achievement motivation.